A survey of the use of operational research in decisions made by micro, small and medium-sized enterprises in Macedonia - Cvetkoska, Violeta (Croatian Operational Research Society, 2016)
We live in a complex world and managers of organizations are constantly facing numerous challenges. Good decisions, i.e., better outcomes for organizations, require use of the powerful discipline Operational Research (OR)/Management Science (MS). Organizations applying this discipline have achieved significant benefits such as cost reduction, increased revenues, increased market share, higher quality, improved productivity, improved performance, better customer service, etc. The aim of this paper is to examine whether managers of micro, small and medium-sized enterprises in Macedonia use OR models for supporting decision-making processes, where OR models, methods and techniques are commonly used, and what benefits achieved in using quantitative OR models, methods and techniques. The survey was conducted using a questionnaire distributed electronically to 100 managers of micro, 100 managers of small and 100 managers of medium-sized enterprises. The questionnaires were answered completely by 93 managers of the micro, 73 managers of the small and 71 managers of the medium-sized enterprises, and the questionnaire responses were subsequently analyzed. The answers showed that decisions on running enterprises are made intuitively by 90% of managers of the micro, 78% of managers of the small, and 55% of managers of the medium-sized enterprises, while quantitative OR models for supporting the decision-making process are used by 10% of managers of the micro, 22% of managers of the small, and 45% of managers of the medium-sized enterprises. Applied in the micro, small and medium-sized enterprises are inventory models, time series analysis and forecasting, whereas micro and mediumsized enterprises rely on decision analysis. Small and medium-sized enterprises use breakeven analysis, assignation, linear programming, and project management. The OR models and methods used in running the respective enterprises led to the following results: optimal inventory level, cost reductions, revenue growth, forecasted sales, increased sales, production optimization, improved quality, better planning of activities, more efficient allocation of staff, absence of complaints and increased customers satisfaction.
Keywords: decision making, managers, operational research, micro enterprises, small enterprises, medium-sized enterprises